TIPOLOGI BERAKHLAKUL KARIMAH DALAM MERDEKA BELAJAR - Imamul Muttaqin; Sahrul Maulana; M. Haydar Afief; Khoirun Nisaa; Fi Ramatillah Maulida; Shafira Awaliyah (STAI Ma'had Aly Al-Hikam Malang, 2023)
Education is the process of acquiring knowledge from educators by students. Its purpose is to enhance knowledge and shape good behavior and character. Teachers act as facilitators, while students are the main participants in the teaching and learning activities. The curriculum plays a crucial role in achieving educational goals. The